Ecodevelopmental × Intrapersonal Risk: Substance Use and Sexual Behavior in Hispanic Adolescents - Prado, Guillermo J. (2008)
Hispanic adolescents are a rapidly growing population and are highly vulnerable to substance abuse and HIV infection. Many interventions implemented thus far have been “one size fits all” models that deliver the same dosage and sequence of modules to all participants. To more effectively prevent substance use and HIV in Hispanic adolescents, different risk profiles must be considered. This study’s purpose is to use intrapersonal and ecodevelopmental risk processes to identify Hispanic adolescent subgroups and to compare substance use rates and sexual behavior by risk subgroup. The results indicate that a larger proportion with high ecodevelopmental risk (irrespective of the intrapersonal risk for substance use) report lifetime and past 90-day cigarette and illicit drug use. In contrast, a larger proportion with high intrapersonal risk for unsafe sex (irrespective of ecodevelopmental risk) report early sex initiation and sexually transmitted disease incidence. Implications for intervention development are discussed in terms of these Hispanic adolescent subgroups.